Mitigating Present Bias with Immediate Narratives on Plastic Usage: An Experimental Study in Makassar City - Anhar Dana Putra; Muhammad Reza Firmansyah (Psychology Program, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2026)
Prior research has demonstrated that present bias impedes the adoption of pro-environmental behaviors, such as reducing the consumption of single-use plastics in everyday life. Van der Linden (2015) found that those who utilize disposable plastics exhibit more vulnerability to present bias, displaying a preference for immediate convenience at the expense of long-term environmental consequences. Nevertheless, despite the urgent plastic waste problem in Indonesia, there is still a shortage of extensive literature on effective solutions to this issue. This study investigates whether immediate impact narratives on climate change can affect people's intentions to reduce the consumption of single-use plastic. Using a between-subject design experiment, 90 individuals were randomly divided into three groups. Group A was shown with a vignette containing narratives that conveyed the immediate impacts of climate change. Group B, on the other hand, was shown a vignette containing narratives that conveyed long-term impact of climate change. Group C did not receive any vignette. Afterwards, all participants filled out a questionnaire that assessed their intention to reduce the consumption of single-use plastic in the future. The findings revealed substantial disparities among the groups, with Group A demonstrating a greater intention to reduce the consumption of single-use plastics in comparison to Group B and C. These findings indicate that by using immediate impact narratives, present bias can be mitigated and effective interventions can eventually be devised to gradually reduce the consumption of single-use plastic in the long run.